Compositional diversity of iridoids, phenolic compounds, and crocins in Gardenia jasminoides fruits of different varieties - Tian, Ye; Zhou, Ying; Zhang, Youzuo; Ni, Qinxue; Yang, Baoru (Elsevier BV, 2026)
By using UPLC-ESI-MS/MS2 and HPLC-DAD, 62 phytochemicals were characterized from fruits of Gardenia jasminoides Ellis (GF) and G. jasminoides var. radicans Makino (GFV), mainly covering iridoids, crocins, hydroxycinnamic acids, and flavonols. Most identified compounds were found at higher levels in GF than in GFV. A clear compositional diversity was observed between hulls and dehulled fractions of fruits. The dehulled parts had higher levels of iridoids (71–75 vs. 61–66 mg/g dry weight, DW; 3 biological replicates applied) and crocins (14–21 vs. 10–17 mg/g DW), whereas minor phytochemicals such as hydroxycinnamic acids and flavonols were concentrated in the hulls. The dominant phytochemicals in the dehulled fruits were geniposide (44–46 mg/g DW) and crocin I (11–16 mg/g DW). In contrast, geniposide (20–28 mg/g dry weight, DW) and gardenoside (19–24 mg/g DW) represented half percentage of the total content of phytochemicals identified in the hulls.